Crop-weed competition in onion (Allium cepa) under mid-hill condition of North-west Himalayas* - PRAKASH, VED; KUMAR, NARENDRA; SRIVASTVA, A K (The Indian Journal of Agricultural Sciences, 2011)
An experiment was conducted during winter season of 1999-000 and 2000-2001 to find out the critical period of crop-weed competition in onion (Allium cepa L.) with a set of 10 treatments comprising weedy and weed-free conditions up to 30, 60, 90, 120 days after transplanting and harvest. Weed competition index increased with increase in duration of weedy condition ranging from 2 to 77.9. On the other hand, increase in weed-free period for different duration from transplanting to 90 days after transplanting decreased weed competition index to 1.7 from 77.9"Weed-free condition beyond 90 days after transplanting did not bring significant impr~vement in bulb yield. The critical period ofcrop- weed competition in onion was observed to be between 30-90 days after transplanting. Hence, the crop should be kept weed-free during this period to realize the higher bulb yield and monetary returns.'>p/>